An ancient, MHC-linked, nonclassical class I lineage in cartilaginous fish - Almeida, Tereza (J Immunol, 2020)
Cartilaginous fishes, or Chondrichthyans, are the oldest jawed vertebrates having an adaptive immune system based on the major histocompatibility complex (MHC) and immunoglobulin superfamily-based (IgSF) antigen receptors. In this basal group of jawed vertebrates we identified a third nonclassical MHC class I lineage (UDA), which is present in all species analyzed within the two major cartilaginous subclasses, Holocephali (chimaeras) and Elasmobranchii (sharks, skates, and rays). The deduced amino acid sequences of UDA have eight out of nine typically invariant residues that bind to the N- and C- termini of bound peptide found in most vertebrae classical class I (UAA); additionally, the other predicted 28 peptide binding residues are perfectly conserved in all elasmobranch UDA sequences. UDA is distinct from UAA in its differential tissue distribution and its lower expression levels, and is mono- or oligomorphic unlike the highly polymorphic UAA. UDA is in low copy number in elasmobranchs but is multicopy in the holocephalan spotted ratfish (Hydrolagus colliei). Using a nurse shark (Ginglymostoma cirratum) family, we found that UDA is MHC-linked but separable by recombination from the tightly linked cluster of UAA, TAP and LMP genes, the so-called class I region found in most nonmammalian vertebrates. UDA has predicted structural features that are similar to certain nonclassical class I genes in other vertebrates, and, unlike polymorpic classical class I, we anticipate that it may bind to a conserved set of specialized peptides.